2011
DOI: 10.1007/s00034-011-9343-4
|View full text |Cite
|
Sign up to set email alerts
|

Set-Reset Flip-Flop Circuit with a Simple Output Logic

Abstract: The equation of the plane (EOP) in analytic geometry is used to build a logic dynamic architecture, i.e., a combination of set-reset flip-flop (SR-FF) and basic logic gates. This is achieved by using two of the variables in the EOP as the input signals of the SR-FF and the remaining variable as the output signal. This theoretical proposal for mixing the SR-FF and the basic logic gates is confirmed experimentally by means of a simple electronic implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Apart from designing logic gates many efforts have been made to exploit nonlinear systems to construct memory devices. Chaos based SR flip-flop from two cross coupled Chua's circuit, SR flip-flop using reconfigurable analog block, set-reset latch in noise assisted bistable system, R-S flip-flop from two-cross coupled quasiperiodically driven MLC circuit are few examples for constructing memory latch using nonlinear systems 26,32,56,57 . In the present work, we demonstrate how the simple SC-CNN based periodically driven MLC circuit (6) can produce a consistent and complete RS flip-flop.…”
Section: Set-reset Memory Latchmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from designing logic gates many efforts have been made to exploit nonlinear systems to construct memory devices. Chaos based SR flip-flop from two cross coupled Chua's circuit, SR flip-flop using reconfigurable analog block, set-reset latch in noise assisted bistable system, R-S flip-flop from two-cross coupled quasiperiodically driven MLC circuit are few examples for constructing memory latch using nonlinear systems 26,32,56,57 . In the present work, we demonstrate how the simple SC-CNN based periodically driven MLC circuit (6) can produce a consistent and complete RS flip-flop.…”
Section: Set-reset Memory Latchmentioning
confidence: 99%
“…In ref. 56,57 the equation of the plane in analytical geometry has been used to build a contribution of SR flip-flop and basic logic gates 56,57 . Storni et al have investigated LSR by extending the analysis to a three well potential to realize XOR logic gates 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The market of mobile phones and the field of internet of things both are increasing aggressively 1,2 . In addition to that, basic digital camera, tablet, laptop, advancement of different kinds of wearable information devices or health‐care devices are in huge demand 3,4 . These equipment are generally battery‐operated; therefore, reduction in power consumption is very crucial, in order to operate them for longer time 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Cafagna and Grassi proposed chaos based S-R flip-flop from two cross coupled NOR gates implemented by a single Chua's circuit 16 . Campos-Canton et al 17 reported a reconfigurable analog block able to simulate different logic gates and S-R flip-flop with the logic output signal based on the equation of the plane in analytic geometry. They validated their results with experiments 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Campos-Canton et al 17 reported a reconfigurable analog block able to simulate different logic gates and S-R flip-flop with the logic output signal based on the equation of the plane in analytic geometry. They validated their results with experiments 17 . Kohar and Sudeshna Sinha demonstrated how noise allows a bistable system to behave as a Set-Reset latch as well as a logic gate 11 .…”
Section: Introductionmentioning
confidence: 99%